(untitled) (Metallurgy and Foundry Engineering, 2017)
The two-component melt-spun (TCMS) Fe71.25Si9.5B14.25In5 alloy was produced from Fe75Si10B15 and Fe67.5Si9B13.5In10 alloys. The microstructure of the TCMS alloy was investigated by means of scanning electron microscopy (SEM) and X-ray diffraction (XRD). A tensile test of the alloy resulted in a tensile strength of Rm = 1040 MPa, yield strength Re = 919 MPa, total plastic elongation etot = 3.29%, and traces of plastic deformation on the surface of the Fe-Si-B-In TCMS sample. Microstructural analysis of the amorphous/crystalline composite and tensile sample free surface show the reason for the ductility of the sample in relation to the Fe75Si10B15 alloy.